2022
DOI: 10.1002/jbm.a.37450
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of methacrylated gelatin /layered double hydroxides nanocomposite cell‐laden hydrogel bioinks with high printability for 3D extrusion bioprinting

Abstract: Layered double hydroxides (LDHs) offer unique source of inspiration for design of bone mimetic biomaterials due to their superior mechanical properties, drug delivery capability and regulation cellular behaviors, particularly by divalent metal cations in their structure. Three-dimensional (3D) bioprinting of LDHs holds great promise as a novel strategy thanks to highly tunable physiochemical properties and shear-thinning ability of LDHs, which allow shape fidelity after deposition. Herein, we introduce a strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…As cartilage is a hypocellular tissue with extremely limited regeneration potential, several 3D bioprinting approaches with a variety of nanocomposite additives have been researched for their chondrogenic and therapeutic potentials. One of these examples includes the integration of methacrylated gelatin layered with layered hydroxide nanoparticles for the formulation of highly printable hydrogel bioink [156]. Here, hydroxide particles were investigated for their mechanical properties that may be able to assist the soft nature of methacrylated gelatin to provide a mechanically durable printed construct.…”
Section: Nanomaterials Composites For Cartilage Bioprintingmentioning
confidence: 99%
“…As cartilage is a hypocellular tissue with extremely limited regeneration potential, several 3D bioprinting approaches with a variety of nanocomposite additives have been researched for their chondrogenic and therapeutic potentials. One of these examples includes the integration of methacrylated gelatin layered with layered hydroxide nanoparticles for the formulation of highly printable hydrogel bioink [156]. Here, hydroxide particles were investigated for their mechanical properties that may be able to assist the soft nature of methacrylated gelatin to provide a mechanically durable printed construct.…”
Section: Nanomaterials Composites For Cartilage Bioprintingmentioning
confidence: 99%
“…Nadernezhad et al demonstrated that agarose and Laponite nanosilicates not only developed nanocomposite shear thinning of nanocomposite bioinks for extrusion 3D bioprinting applications but also significantly improved the bioactivity of nanocomposite hydrogels with increased metabolic activity of encapsulated cells and the ability of cells to extend and change their morphology [206]. Alarçin et al optimized the printability of methacrylated gelatin (gelatin methacrytoyl, GelMA) with layered double hydroxides (LDHs) [207]. Their results indicated that the addition of LDHs into the GelMA network could improve the physical and biological properties of the nanocomposite scaffolds.…”
Section: Advances and Limitations In 3d Bioprintingmentioning
confidence: 99%
“…These limitations can be minimized, and even novel properties on polymer-based materials can be achieved, by the presence of a wide variety of inorganic structures. Especially for bone-related applications, hybrid materials based on the combination of LDH and polymers are promising to owe to: (i) the enhancement of the mechanical properties of the resulting composite [ 271 , 277 ]; (ii) the improvement of osteogenic differentiation associated with the release of Mg 2+ ions from the LDH structure and the alkaline microenvironment [ 272 , 278 ]; (iii) good biocompatibility, low toxicity and structural homogeneity [ 169 ]; (iv) thermal stability and drug release of bioactive compounds from the intercalated LDH structure [ 279 ]; (v) thermal insulation from the exothermic polymerization process, and (vi) creation of surface irregularities that could benefit osteointegration [ 272 ].…”
Section: Organic Polymers and Layered Double Hydroxides Nanocomposite...mentioning
confidence: 99%
“…LDH-based hybrid materials were also proposed for bone-related applications when combined with pristine or modified natural polymers to improve their physical and biological properties. Alarçir et al [ 278 ] combined a Mg 4 Al intercalated with carbonate ions, gelatin methacryloyl (GelMA) and alginate to produce printable bioinks for additive manufacture to generate biocompatible hydrogel scaffolds. The presence of the inorganic phase in the composite aided the filament formation and the stackability of layers of filaments to yield different printed shapes.…”
Section: Organic Polymers and Layered Double Hydroxides Nanocomposite...mentioning
confidence: 99%